2018
DOI: 10.1017/s1047951118001300
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis sepsis and endocarditis in a newborn following lotus birth

Abstract: A term newborn, who underwent lotus birth, developed Staphylococcus lugdunensis sepsis and endocarditis on the 1st day of life. This case reports an uncommon pathogen known to cause destructive endocarditis in the adult and paediatric populations, causing endocarditis in a neonate. We speculate that lotus birth, an atypical birthing practice, may have contributed to the development of this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Similar to many reports of invasive infections caused by SL in adults [5,[29][30][31][32] and a few case reports in children [12,13,33], in our study population two cases were identified. This is consistent with previous studies describing a fulminant course of infection as rapidly progressive endocarditis and CLABSI [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to many reports of invasive infections caused by SL in adults [5,[29][30][31][32] and a few case reports in children [12,13,33], in our study population two cases were identified. This is consistent with previous studies describing a fulminant course of infection as rapidly progressive endocarditis and CLABSI [34].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies of SL infections in children are limited to case reports, with results from a small series doubting its role as a pathogen [10]. When SL was considered the causative agent of infection, it mostly involved bloodstream infections [11][12][13][14], skin infections [15] and foreign body related infections [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the relatively low level of virulence, immature infants with sepsis caused by these pathogens present a wide range of clinical symptoms ( Lauterbach et al 2016 ). It was shown that S. lugdunensis was responsible for sepsis and endocarditis on the 1st day of life in a term newborn, which underwent lotus birth ( Ittleman and Szabo 2018 ). In contrast, S. aureus strains often exhibit a vast arsenal of toxins and enzymes involved in staphylococcal pathogenesis.…”
Section: Pathogenicity Of Staphylococcal Bloodstream Infectionsmentioning
confidence: 99%
“…The specific incidence of S. lugdunensis among the neonatal population is unknown, although CONS is the most prevalent infection among the VLBW infants in the neonatal intensive care setting. Our patient is the fourth case of S. lugdunensis sepsis in the neonatal population reported so far [ 12 , 13 , 14 ] (see Table 3 ). The uniqueness of our patient’s disease is due to the fulminant presentation with septic shock needing inotropes, as well as persistent bacteremia with an infected aortic thrombus probably from a previously placed UAC.…”
Section: Discussionmentioning
confidence: 94%